A methodology for transferring principles of plant movements to elastic systems in architecture. (March 2015) - Schleicher, Simon; Lienhard, Julian; Poppinga, Simon; Speck, Thomas; Knippers, Jan
Abstract: In architecture, kinetic structures enable buildings to react specifically to internal and external stimuli through spatial adjustments. These mechanical devices come in all shapes and sizes and are traditionally conceptualized as uniform and compatible modules. Typically, these systems gain their adjustability by connecting rigid elements with highly strained hinges. Though this construction principle may be generally beneficial, for architectural applications that increasingly demand custom-made solutions, it has some major drawbacks. Adaptation to irregular geometries, for example, can only be achieved with additional mechanical complexity, which makes these devices often very expensive, prone to failure, and maintenance-intensive. Searching for a promising alternative to the still persisting paradigm of rigid-body mechanics, the authors found inspiration in flexible and elastic plant movements. In this paper, they will showcase how today's computational modeling and simulation techniques can help to reveal motion principles in plants and to integrate the underlying mechanisms in flexible kinetic structures. By using three case studies, the authors will present key motion principles and discuss their scaling, distortion, and optimization. Finally, the acquired knowledge on bio-inspired kinetic structures will be applied to a representative application in architecture, in this case as flexible shading devices for double curved facades. Highlights: Plant movements. Kinetic structures. Biomimetics. Facade shading. Compliant mechanisms.